2021
DOI: 10.1145/3425711
|View full text |Cite
|
Sign up to set email alerts
|

Informal Technology Education for Women Transitioning from Incarceration

Abstract: As society increasingly relies on digital technologies in many different aspects, those who lack relevant access and skills are lagging increasingly behind. Among the underserved groups disproportionately affected by the digital divide are women who are transitioning from incarceration and seeking to reenter the workforce outside the carceral system (women-in-transition). Women-in-transition rarely have been exposed to sound technology education, as they have generally been isolated from the digital environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Taking a desistance mindset, considering digital illiteracy a key criminogenic issue and broadening pre-release planning to include a consideration of digital readiness will be beneficial for tackling recidivism for this group. Relatedly, researchers and policymakers have increasingly recognized the utility of using digital tools for rehabilitation and treatment for prisoners both whilst in prison and after release, such as rehabilitative apps, or digital means of supervision [46][47][48]. Older people in prison must be taught to use such technology for these rehabilitation initiatives to be successful.…”
Section: Plos Onementioning
confidence: 99%
“…Taking a desistance mindset, considering digital illiteracy a key criminogenic issue and broadening pre-release planning to include a consideration of digital readiness will be beneficial for tackling recidivism for this group. Relatedly, researchers and policymakers have increasingly recognized the utility of using digital tools for rehabilitation and treatment for prisoners both whilst in prison and after release, such as rehabilitative apps, or digital means of supervision [46][47][48]. Older people in prison must be taught to use such technology for these rehabilitation initiatives to be successful.…”
Section: Plos Onementioning
confidence: 99%
“…Taking a desistance mindset, considering digital illiteracy a key criminogenic issue and broadening pre-release planning to include a consideration of digital readiness will be beneficial for tackling recidivism for this group. Relatedly, researchers and policymakers have increasingly recognized the utility of using digital tools for rehabilitation and treatment for prisoners both whilst in prison and after release, such as rehabilitative apps, or digital means of supervision (e.g., Hwang et al, 2021;Perdacher et al, 2022;Seo et al, 2021). Older people in prison must be taught to use such technology for these rehabilitation initiatives to be successful.…”
Section: Key Findings and Implicationsmentioning
confidence: 99%
“…For example, systematic empirical data that directly compare formerly incarcerated women's digital skills and access with those with no criminal justice involvement or those of formerly incarcerated men do not exist at this point. However, previous studies have shown that formerly incarcerated women face additional barriers in reentry education and employment (Curcio & Pattavina, 2018;Emerson, 2018;Seo et al, 2020;Seo et al, 2021), which can then affect their digital experiences. Specifically, Curcio and Pattavina found that women with criminal justice involvement face more barriers to employment compared with similarly situated men (Curcio & Pattavina, 2018).…”
Section: Scholarly and Policy Implicationsmentioning
confidence: 99%